Vitamin A and skeletal anomalies in Pacu larvae - Lopes, Taís Silva; Bonichelli, Rosangela Kiyoko Jomori; Carani, Fernanda [UNESP]; Portella, Maria Célia [UNESP] (Universidade Federal de Santa Maria, 2025)
Vitamin A (VA) has a central role in the skeletal formation of fish larvae as it participates in the growth and development of cells and tissues during embryogenesis. We evaluated the effect of VA on the incidence of skeletal anomalies in the production of Piaractus mesopotamicus (P. mesopotamicus) larvae. The experiment was carried out using a total of 12,800 newly hatched larvae and included two phases: the first phase - was installed with two treatments A0, Artemia nauplii, and A50, Artemia nauplii enriched with 50,000 UI of retinol acetate (AR), with eight replicates each an distributed in 16 100-L tanks (8 larvae.L-1), the second phase was installed with the larvae for each treatment in the first phase and redistributed in 32 50-L tanks and received four formulated diets supplemented or not with vitamin A: D0, D30, D60, and D120 (addition of 0, 30,000, 60,000, and 120,000 UI of AR.kg-1 of diet, respectively), with four replicates. The feeding transition was performed gradually, for three days, until the live food was suppressed. At the end of the larvae were counted to evaluate the survival rate, and a sample was evaluated for performance, incidence of skeletal anomalies, and expression of genes related to possible skeletal anomalies. The results indicated that the A0D30 treatment favored growth and showed the lowest incidence of skeletal anomalies.

A vitamina A (VA) tem um papel central na formação do esqueleto de larvas de peixe, uma vez que participa no crescimento e desenvolvimento de células e tecidos durante a embriogênese. O objetivo do presente trabalho foi avaliar o efeito da VA na incidência de anomalias esqueléticas na larvicultura de Pacu (Piaractus mesopotamicus). O experimento foi realizado com 12.800 larvas recém-eclodidas e incluiu duas fases: na primeira fase foram utilizados dois tratamentos A0, náuplios de Artemia, e A50, náuplios de Artemia enriquecidos com 50.000 UI de acetato de retinol (AR), com oito réplicas cada e distribuídas em 16 tanques de 100-L (8 larvas. L-1); a segunda fase foi realizada com as larvas de cada tratamento da primeira fase e redistribuídas em 32 tanques de 50 L, que receberam quatro dietas formuladas suplementadas ou não com vitamina A: D0, D30, D60 e D120 (adição de 0, 30.000, 60.000 e 120.000 UI de AR.kg-1 de dieta, respectivamente), com quatro repetições. A transição alimentar foi realizada de forma gradual, durante três dias, até que o alimento vivo fosse suprimido. Ao final, as larvas foram contadas para avaliar a taxa de sobrevivência, e uma amostra foi avaliada quanto ao desempenho, incidência de anomalias esqueléticas e expressão de genes relacionados a possíveis anomalias esqueléticas. Os resultados indicam que o tratamento A0D30 favoreceu o crescimento e apresentou a menor incidência de anomalias esqueléticas.
Vitamina A e anormalidade esqueléticas em larvas de Pacu
Keywords: hypervitaminosis A; larviculture; skeletal deformity; vitamin deficit; deformidades esqueléticas; déficit de vitamina; hipervitaminose A; larvicultura de peixes